STUDY ON THE INFLUENCE OF THE ANGULAR DIRECTION OF ALUMINUM COOLING FINS ON THE WORKING TEMPERATURE OF SOLAR PANELS - Binyamin, Binyamin; Riswan, Muhammad; Nugroho, Andi; Julianto, Eko (Media Mesin: Majalah Teknik Mesin, 2026)
The utilization of solar energy through solar panels as a source of electrical energy for households and street lighting is increasing rapidly. However, solar panels face problems related to working temperature. When the absorption of solar radiation is too high, it results in a decrease in efficiency. High temperatures cause solar panels to produce lower energy than in cold conditions. Therefore, the purpose of this study was to explore the effect of aluminum cooling fins on solar panels, with variations of fin inclination angles of 30° and 45°, and compared with panels without a cooling system to reduce the working temperature of solar panels by using cooling fins and air blowing media. The results showed that at an angle of 30°, the panel temperature was 43.60°C at the 13th iteration, with a temperature drop of about 3.13%. At an angle of 45°, the temperature obtained was 41.80°C with a temperature drop of about 6.68%. Meanwhile, the uncooled condition reached a maximum temperature of 44.40°C. No cooling causes the panel temperature to be higher, and the 45° angle provides a better cooling effect than the 30° angle, although the difference is not very significant when compared to the uncooled condition.